Photonic crystal nanobeam cavities with lateral fins - Liu Zhonghe (De Gruyter, 2021)
We present the design, fabrication, and characterization of suspended arrays of small volume, high quality factor (Q) silicon nitride photonic crystal nanobeam (PCNB) cavities with lateral nanorod fin structures. By controlling the alignment position of the fins with respect to the air holes, the resonance wavelength and Q-factor of the PCNB cavities can be tuned to realize the desired performance. Measured tunable range of 2 × 104 and 10 nm is achieved for Q-factor and resonance wavelength, respectively, with the highest Q-factor measured at 2.5 × 104. Incorporating such nanorod fins into the nanobeam cavity is demonstrated to provide improved mechanical support, thermal transport, and channels of lateral carrier injection for the suspended PCNB. The proposed PCNB cavities with lateral fins are advantageous for energy efficient, ultra-compact lasers, modulators, filters, and sensors.